Cost-Emission Scheduling under Uncertainty in a Smart Grid with Wind Power and PHEVs - Zhang Xiaohua; Xie Jun; Li Zhenkun (Institute of Advanced Engineering and Science, 2014)
The rapid development of plug-in electric vehicles (PHEVs) and wind power brings new challenges to power system security and economic operation. Traditional deterministic models fail to capture their extra characteristics. In this paper, PHEVs, wind power and thermal units are studied. The scheduling model with PHEVs and wind power is more complex, which minimizes the cost-emission while considering the uncertainty of wind power and load, the smart charging/discharging of PHEVs, the coordination of wind power and PHEVs. The multi-scenario simulation is presented in the random variable discretization. Numbers of representative scenarios is chosen, so that the original objective of the smart grid is within an acceptable level. Then the multi-agent system(MAS)technology is proposed to divided a day is into 24 time intervals, and each time interval is managed by a work agent to produce a solution set for the time interval. The wind power, PHEVs and thermal units are coordinated by the work agent. 24 work agents are managed a coordination agent that would coordinate the solutions of the work agents. Finally, a smart grid of 10 thermal units, a wind farm and PHEVs are used to demonstrate the effective of the proposed model. The results show that the smart grid can use the wind power and PHEVs most effectively, can greatly cut the operation cost and carbon emission. By the tradeoff between the weight factor of cost and emission, the balance of cost and emission can reach. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4953